The Paradigm of the General Principles of Good Governance as Examination Method of Indonesian Presidential Impeachment based on the Perspective of Ethical Control - Nadir Nadir (Faculty of Law, Universitas Padjadjaran, 2020)
This study aims to reveal the paradigm of General Principles of Good Governance as a method of examination for Indonesian presidential impeachment based on the perspective of ethical control. This study employed the method of legal research. It was carried out to reveal principles and basis of (dogmatic or doctrinal) philosophy of positive law. In addition, the study is legal discovery in-concreto that is feasible to be applied to resolve a certain legal case. This study exposes that one of the legal reasons for the termination of the President of Indonesia is despicable deeds. It is determined as an act of President that degrade human characters. Hermeneutically, the meaning of “despicable deeds” may cover criminal acts and ethical actions. Therefore, the meaning of “despicable deeds” in this study is limited into acts of ethics infringement related to the General Principles of The Good Governance. The President can be terminated from the office when there is a violation to the General Principles of the Good Governance since the principles are the ethical principles of government. The principles contain honesty, accuracy, purity, balance, and legal certainty. These principles are the items that bring solution and reference for the House of Representatives (DPR) and the People’s Consultative Assembly (MPR) and the Constitutional Court. Theoretically, there is no norm, either of the 1945 Constitution or of other regulations, which limit the interpretation of “despicable acts” as a reflection of the acts of the President to be classified into ethical conducts. Therefore, the application of the General Principles of Good Governance as method of examination for the presidential impeachment is a new paradigm from the perspective of ethical control in Indonesia. Paradigma Penerapan Asas-Asas Umum Pemerintahan Yang Baik (AUPB) sebagai Batu Uji Pemberhentian Presiden Indonesia berdasarkan Perspektif Pengawasan EtikAbstrakTujuan penelitian ini untuk menemukan Paradigma Pemberhentian Presiden Indonesia dengan Batu Uji Asas-Asas Umum Pemerintahan Yang Baik dalam Perspektif Pengawasan Etik. Metode penelitian ini adalah penelitian hukum (legal research), yaitu: suatu penelitian yang dikerjakan dengan tujuan untuk menemukan asas dan dasar falsafah (dogma atau doktrin) hukum positif, di samping itu penelitian berupa usaha penemuan hukum in concreto yang layak diterapkan untuk menyelesaikan suatu perkara hukum tertentu. Hasil penelitian ini menunjukkan bahwa salah satu alasan hukum pemberhentian Presiden Indonesia adalah perbuatan tercela sebagai refleksi perbuatan merendahkan martabat Presiden. Secara hermeneutik makna “perbuatan tercela” dapat dikualifisir masuk ke dalam perbuatan dari segi pidana dan perbuatan dari segi etika, oleh karena itu makna “perbuatan tercela” dalam penelitian ini dapat dikualifisir masuk ke dalam perbuatan melanggar etika, sehingga masuk ke dalam AUPB dan Presiden dapat diberhentikan dalam masa jabatannya. AUPB dimaksud adalah asas etis pemerintahan yang terkandung dalamnya adalah asas kejujuran, kecermatan, kemurnian, keseimbangan, dan kepastian hukum. Asas ini masuk ke dalam AUPB yang dapat dijadikan solusi kaidah penuntun dan rujukan bagi DPR-MPR dan Mahkamah Konstitusi Republik Indonesia. Secara teoritis tidak ada batasan norma baik norma hukum yang tertuang di dalam UUD RI Tahun 1945 maupun norma hukum yang ada di luar UUD RI Tahun 1945 melarang interpretasi “perbuatan tercela” sebagai refleksi perbuatan merendahkan martabat Presiden masuk ke dalam perbuatan melanggar etika, sehingga penerapan Asas-Asas Umum Pemerintahan Yang Baik (AUPB) sebagai batu uji pemberhentian Presiden merupakan paradigma baru dalam perspektif pengawasan etik di Indonesia.Kata kunci: asas-asas umum pemerintahan yang baik, pemberhentian presiden, pengawasan etik.DOI: https://doi.org/10.22304/pjih.v7n2.a1